Analysis of Spatial and Crop Specific Mechanization Diversities in India - Chouhan, G. S.; Singh, G. (Journal of Agricultural Engineering, 2015)
A mechanization index (MI) based on the share of cost of use of mechanical power operated farm equipment over total cost of use of animate and mechanical power operated farm equipment was estimated based on secondary data for the year 2008-09. The analysis revealed a large diversity in MI for different crops at state and National levels. Wheat crop recorded highest MI index of 40.77% at the national level and a highest of 56.17% in Punjab. Paddy crop recorded 35.58% MI in Punjab, but at the national level it was only 17.40 per cent. The MI of other crops varied as rapeseeds and mustard (32.52%), gram (31.91%) and sugarcanes (9.09%). The analysis also revealed that states having higher MI or tractor intensity recorded better crop yield.